PENGARUH PENGUNAAN APLIKASI BELANJA ONLINE TERHADAP PERILAKU KONSUMTIF - Zahrah, Alika; Mayasari, Mayasari; Tayo, Yanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research is motivated by the presence of an online shopping application that is currently being discussed, namely Shopee. The Shopee application is in great demand by teenagers to adults, but not a few also think that the Shopee application can have a bad influence on its users. However, there is also a positive side that can be taken from the Shopee application, namely as a means of purchasing the desired goods or services online without having to leave the house. Seeing this phenomenon, researchers are interested in being used as research on the effect of using the Shopee application on consumptive behavior. This study aims to find out how the intensity and content of messages using the Shopee application on consumptive attitudes of students of the Communication Studies Program at Singaperbangsa Karawang University class of 2017. This study uses a quantitative approach with multiple linear regression analysis with support from Uses and gratification Theory with research subjects namely Communication Science students Unsika communication science class 2017. The data collection techniques in this study used a questionnaire/questionnaire and literature study. The data analysis technique used was descriptive analysis, classical assumptions, and multiple regression analysis. The results of this study found that the intensity of the use of the Shopee application had an effect on the consumptive behavior of students of the 2017 Communication Science Study Program, Singaperbangsa Karawang University, and also the message content of the use of the Shopee application affected the consumptive behavior of students of the 2017 Communication Studies Program, Singaperbangsa Karawang University.